2023
DOI: 10.1002/jum.16361
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Workplace Sexual Harassment Experienced by Medical Sonographers

Sue Y. Yi,
Naiim S. Ali,
Kenneth S. Lee
et al.

Abstract: ObjectiveTo assess the prevalence and impact of sexual harassment among a nationwide sample of medical sonographers.MethodsA survey was distributed anonymously to a convenience sample of medical sonographers via email contacts and sonographer‐specific social media pages. Data were analyzed to determine respondent demographics, the prevalence of sexual harassment in the last 2 years, the type and severity of harassment experienced, demographics of perpetrators, personal and institutional responses to such exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…27,28 In other words, the CBI may be particularly well-suited to study how burnout interacts with sonographers' experiences in the workplace at the individual, interpersonal, and work environment levels. A recent sonography study from Yi et al 15 highlighted associations between experiences of sexual harassment and adverse psychological outcomes such as depression, sleep loss, and anxiety. Others may also seek to use the CBI to assess client burnout's relationship with hazards arising from interpersonal domains of work such as verbal, physical, and sexual harassment.…”
Section: Assessing and Conceptualizing Occupational Burnout In Sonogr...mentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 In other words, the CBI may be particularly well-suited to study how burnout interacts with sonographers' experiences in the workplace at the individual, interpersonal, and work environment levels. A recent sonography study from Yi et al 15 highlighted associations between experiences of sexual harassment and adverse psychological outcomes such as depression, sleep loss, and anxiety. Others may also seek to use the CBI to assess client burnout's relationship with hazards arising from interpersonal domains of work such as verbal, physical, and sexual harassment.…”
Section: Assessing and Conceptualizing Occupational Burnout In Sonogr...mentioning
confidence: 99%
“…Recent studies of sonographers have indicated that most sonographers experience moderate-to-high levels of occupational burnout, 11 -13 as well as a nearly 90% prevalence of factors related to occupational burnout including work-related musculoskeletal disorders (WRMSD) over the past year 14 and instances of sexual harassment over the past 2 years. 15 A recent systematic review of studies over the past two decades also highlighted the relationship of high workloads and the burden of adverse interactions in patient encounters with occupational burnout. 16 At this point, we have compelling evidence of specific problems that need immediate attention.…”
mentioning
confidence: 99%